2014 IEEE International Conference on Big Data (Big Data) 2014
DOI: 10.1109/bigdata.2014.7004238
|View full text |Cite
|
Sign up to set email alerts
|

Virtual chunks: On supporting random accesses to scientific data in compressible storage systems

Abstract: Abstract-Data compression could ameliorate the I/O pressure of scientific applications on high-performance computing systems. Unfortunately, the conventional wisdom of naively applying data compression to the file or block brings the dilemma between efficient random accesses and high compression ratios. Filelevel compression can barely support efficient random accesses to the compressed data: any retrieval request need trigger the decompression from the beginning of the compressed file. Block-level compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In future, we will integrate the proposed caching mechanism to other systems such as file compression [62,63], data provenance [64,65] and job scheduling [66]. We plan to further investigate the tradeoff between performance (for example, GPU acceleration [67]) and cost (for example, scientific applications on EC2 [68]) with the introduction of memoryclass cache, and explore the viability to extend the current approach into incremental mechanisms [69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…In future, we will integrate the proposed caching mechanism to other systems such as file compression [62,63], data provenance [64,65] and job scheduling [66]. We plan to further investigate the tradeoff between performance (for example, GPU acceleration [67]) and cost (for example, scientific applications on EC2 [68]) with the introduction of memoryclass cache, and explore the viability to extend the current approach into incremental mechanisms [69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…This section presents some real systems that have adopted ZHT as a building block. It also leads to additional publications .…”
Section: Zht As a Building Block For Distributed Systemsmentioning
confidence: 99%
“…It is not uncommon to deal with large objects in a distributed system. In scientific computing, for example as our prior work showed, datasets were so large that they were usually compressed to be serialized onto the hard disk. As another example, in our previous work on implementing a distributed file system , we showed that a large directory composed of thousands of small files could result in a huge metadata blob stored in a distributed key‐value store .…”
Section: Design and Analysismentioning
confidence: 99%